2018
DOI: 10.37358/mp.18.1.4972
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study Between Tissues Induced Immunohistochemical Changes of Thread Granulomas and Textile Allografts

Abstract: Since the time of their introduction into medical practice, biomesh were criticized for their lack of tissue integration and the rejection due to the organism reaction for an element that is not autologous. The mechanisms by which these changes of contact between the tissue and the foreign material were produced were initially incompletely understood, but over time the involvement of the immune system mediated by the cellular or humoral local inflammatory reaction was established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Propofol was used for induction and maintenance. One of its main advantages is the ease and speed with which the patient wakes up, and also a low incidence of postoperative nausea and vomiting (8)(9)(10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Propofol was used for induction and maintenance. One of its main advantages is the ease and speed with which the patient wakes up, and also a low incidence of postoperative nausea and vomiting (8)(9)(10).…”
Section: Methodsmentioning
confidence: 99%
“…shown that there is a large difference in the inflammatory capacity of the alloplastic material used, which is influenced by the density of the mesh (14). The presence of smaller holes than 1 mm in the mesh, produces more pronounced inflammation and fibrosis, while larger holes give less fibrotic reaction, lack of keloid scar and conserved the elasticity of the inguinal region (1,8,(14)(15)(16)(17).…”
Section: Clinical Studies and Animal Experiments Havementioning
confidence: 99%
“…The laparoscopic approach to these hydatid localizations is less common (17.5% of cases) and more frequently employed in the tail of pancreas localizations. This approach offers significant benefits over open surgery, which typically involves extensive incisions, such as median or subcostal laparotomies, predisposing patients to wound infections, foreign body reactions such as seromas and granulomas, and incisional hernias [ 44 ].…”
Section: Reviewmentioning
confidence: 99%
“…The mesh with large pores and low weight was employed as there was low contact between the allograft and the body's own tissues, which led to improved acceptance of the alloplastic material by the host organism. The presence of small holes in the mesh (<1 mm) pronounced the inflammatory process and fibrosis, while larger holes provided less fibrotic reaction, and conserved the elasticity of the inguinal region and lack of keloid scar (15)(16)(17).…”
Section: Distribution Of Patients With Postoperative Complicationsmentioning
confidence: 99%